Pengaruh Struktur Kepemilikan, Corporate Social Responsibility, Kebijakan Hutang Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Moderasi - Suripto Suripto; Pipih Niviyanti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the influence of Managerial Ownership Structure, Institutional Ownership Structure, Corporate Social Responsibility, and Debt Policy on Firm Value with Financial Performance as a moderator. The research was conducted by analyzing the financial reports of companies listed on the Kompas 100 Index of the Indonesia Stock Exchange (IDX) from 2018 to 2022. The sample consisted of 79 companies selected using a saturation sampling technique. The data used in this study were secondary data in the form of financial reports from each sampled company. The research methodology employed panel data regression, and the analysis was conducted using EViews 12 Student Version Lite software. The study found that the Random Effect Model (REM) was the best-fitting model. The results indicated that Managerial Ownership Structure, Institutional Ownership Structure, and Corporate Social Responsibility significantly influence Firm Value, while Debt Policy does not. Additionally, Financial Performance does not moderate the influence of Managerial Ownership Structure, Institutional Ownership Structure, Corporate Social Responsibility, and Debt Policy on Firm Value.